Chromatin modifications and the DNA damage response to ionizing radiation - Pandita, Tej K.; Kumar, Rakesh; Horikoshi, Nobuo; Singh, Mayank; Gupta, Arun; Misra, Hari S.; Albuquerque, Kevin; Hunt, Clayton R. (Frontiers in Oncology, 2013)
In order to survive, cells have evolved highly effective repair mechanisms to deal with the potentially lethal DNA damage produced by exposure to endogenous as well as exogenous agents. Ionizing radiation exposure induces highly lethal DNA damage, especially DNA double strand breaks (DSBs), that is sensed by the cellular machinery and then subsequently repaired by either of two different DSB repair mechanisms: 1) non-homologous end-joining (NHEJ), which re-ligates the broken ends of the DNA and 2) homologous recombination (HR), that employs an undamaged identical DNA sequence as a template, to maintain the fidelity of DNA repair. Repair of DSBs must occur within the natural context of the cellular DNA which, along with specific proteins, is organized to form chromatin, the overall structure of which can impede DNA damage site access by repair proteins. The chromatin complex is a dynamic structure and is known to change as required for ongoing cellular processes such as gene transcription or DNA replication. Similarly, during the process of DNA damage sensing and repair, chromatin needs to undergo several changes in order to facilitate accessibility of the repair machinery. Cells utilize several factors to modify the chromatin in order to locally open up the structure to reveal the underlying DNA sequence but posttranslational modification (PTMs) of the histone components is one of the primary mechanisms. In this review, we will summarize chromatin modification by t